2013
DOI: 10.1016/j.clinthera.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and Pharmacokinetics of Delayed-Release Dimethyl Fumarate Administered With and Without Aspirin in Healthy Volunteers

Abstract: In healthy volunteers, DR-DMF was well tolerated over 4 days of dosing, with a PK profile consistent with that previously reported and no evidence of accumulation. Aspirin pretreatment reduced the incidence and intensity of flushing without affecting GI events or the DR-DMF PK profile. Elevated levels of PGD2 in some DR-DMF-treated individuals suggest that flushing may be, at least in part, prostaglandin mediated. ClinicalTrials.gov identifier: ID: NCT01281111.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 21 publications
5
43
0
Order By: Relevance
“…One should recognize that the therapeutic response to DMF in MS is dose dependent (37), and it is possible that individual targets may vary in their sensitivity to different levels of MMF exposure. In this study, the plasma MMF levels obtained in DMF treatment of mice were severalfold higher than those in healthy volunteers treated with DMF doses used in MS (38). Of interest, when DMF was administered in vivo at a higher dose than was used in either our investigation of Nrf2-deficient mice or the study that evaluated HCAR2-deficient mice (35), it was observed that a majority of genes induced in spleen cells by DMF treatment were Nrf2 dependent (4).…”
Section: Discussionmentioning
confidence: 78%
“…One should recognize that the therapeutic response to DMF in MS is dose dependent (37), and it is possible that individual targets may vary in their sensitivity to different levels of MMF exposure. In this study, the plasma MMF levels obtained in DMF treatment of mice were severalfold higher than those in healthy volunteers treated with DMF doses used in MS (38). Of interest, when DMF was administered in vivo at a higher dose than was used in either our investigation of Nrf2-deficient mice or the study that evaluated HCAR2-deficient mice (35), it was observed that a majority of genes induced in spleen cells by DMF treatment were Nrf2 dependent (4).…”
Section: Discussionmentioning
confidence: 78%
“…treatment produces therapeutic MMF plasma levels in SCD mice. In the clinic, DMF is rapidly converted to MMF, which is its major bioactive metabolite (30). In a nonclinical study, DMF delivered to the small intestine of anesthetized rats resulted in the peak plasma levels of MMF within 9-15 minutes (31).…”
Section: Dmf and Mmf Induce Hbf In Erythroid Progenitors Generated Frmentioning
confidence: 99%
“…Elevated levels of prostaglandin D2 in some DMF-treated individuals suggested that flushing may be, at least in part, prostaglandin mediated [Sheikh et al 2013]. In countries where the FDA-approved dosage of 325 mg ASS is not available, lower dosages such as 200 mg ASS may be used.…”
Section: Safety and Tolerability Issues With Dimethyl Fumarate In CLImentioning
confidence: 99%